A Study on the Effects of Personalization and Task Information on Implicit Feedback Performance - White, Ryen W.; Kelly, Diane (15th Annual ACM CIKM Conference on Information and Knowledge Management (CIKM 2006), November 5-11, 2006, Arlington, Virginia, USA, 2006)
While Implicit Relevance Feedback (IRF) algorithms exploit users’ interactions with information to customize support offered to users of search systems, it is unclear how individual and task differences impact the effectiveness of such algorithms. In this paper we describe a study on the effect on retrieval performance of using additional information about the user and their search tasks when developing IRF algorithms. We tested four algorithms that use document display time to estimate relevance, and tailored the threshold times (i.e., the time distinguishing relevance from non-relevance) to the task, the user, a combination of both, or neither. Interaction logs gathered during a longitudinal naturalistic study of online information-seeking behavior are used as stimuli for the algorithms. The findings show that tailoring display time thresholds based on task information improves IRF algorithm performance, but doing so based on user information worsens performance. This has implications for the development of effective IRF algorithms.